Business process reengineering of the supply chain process for cable material in an oil rig construction facility - Lim, Gerard Yuen Chun (2014)
The management of an oil rig construction company wanted to improve information management in the cables supply chain process. The aim was to restructure the process during migration to a new information system to realize reductions in cycle time, operational costs and quality of information processed. Business Process Reengineering (BPR) methodology was used to gain understanding of the process flow, propose redesigns and quantify the benefits using simulation modeling. BPR guidelines for process redesign provided recommendations to improve efficiency by redesigning process flows. Changes to the process would result in elimination of unnecessary non-value-added steps and reduce cycle time. Simulation was used to determine optimal workflow design for the Engineering Coordinator to reduce delays. The proposed configuration of the workflow would result in an 89.23% reduction in average delay experienced to 10.17 hours with a utilization of 71.91% for the Engineering Coordinator.